Redox reactions in chronic pain: mechanisms and relevance in fibromyalgia - Ho, Tim; Ryan, Mark; Holle, Jonas (Frontiers in Pain Research, 2025)
Fibromyalgia (FM) is increasingly recognized as a disorder driven by oxidative stress, mitochondrial dysfunction, and neuroinflammation, contributing to pain sensitization and fatigue. This review explores the role of redox imbalance in FM and evaluates potential therapeutic interventions. A scoping literature search was conducted using PubMed, Scopus, and Google Scholar. Findings indicate elevated oxidative stress markers (MDA, 4-HNE), impaired antioxidant defenses [CoQ10 (Coenzyme Q10), SOD, catalase], and mitochondrial dysfunction in FM patients. Preclinical and small-scale clinical studies suggest potential benefits of NRF2 activation, high-dose thiamine, CoQ10, molecular hydrogen, and oxygen-ozone (O2O3) therapy. However, human trial evidence is limited, and standardized treatment protocols are lacking. Given the absence of robust RCTs, oxidative stress modulation in FM remains investigational. Future research should prioritize high-quality RCTs to establish the efficacy, safety, and clinical application of redox-targeted therapies.